2015
DOI: 10.1007/s11252-015-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urban forms on photosynthetically active radiation and urban greenery in a compact city

Abstract: Urban greenery is increasingly recognized as an important component of urban ecosystems as it provides a range of ecosystem services for environmental and human wellbeing. However, the extent to which the performance of urban greenery is affected by availability of light in high-density urban environment is poorly understood. We examined the effect of shade on the levels of photosynthetically active radiation (PAR) in different urban forms, focusing on urban street canyon, vehicular flyovers, sky terraces, at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This movement of the sun suggests a variation in PAR received at a given location. However, this variation during the year may not be significant in the context of this research due to the higher solar elevation given the equatorial position of Singapore (Tan and Ismail, 2015;Tablada and Zhao, 2016).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This movement of the sun suggests a variation in PAR received at a given location. However, this variation during the year may not be significant in the context of this research due to the higher solar elevation given the equatorial position of Singapore (Tan and Ismail, 2015;Tablada and Zhao, 2016).…”
Section: Resultsmentioning
confidence: 89%
“…This movement of the sun suggests a variation in PAR received at a given location. However, this variation during the year may not be significant in the context of this research due to the higher solar elevation given the equatorial position of Singapore(Tan and Ismail, 2015;Tablada and Zhao, 2016).Figure8shows the role played by shadowing effects on a day-to-day basis. It can be seen from this figure that PAR received on different façades of the buildings was affected by the shadows casted by the building's own façades and surrounding buildings.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Early attempts to generate contextual PAR simulated maps were incorporated in Ecotect (Tan and Ismail, 2015), a currently defunct software that utilized a simplified calculation directly from solar irradiance. More recent methodologies (Subramaniam, 2020, Benis et al, 2017 leverage the partial overlap between the visible wavelength range and photosynthetically active wavelength range of the solar spectrum to simulate PAR.…”
Section: Existing Methodologiesmentioning
confidence: 99%
“…PAR light depends on diurnal and annual temporal variations based on daytime weather and season. Different PAR light is due to the building's shape, orientation, self-shadowing effects, and shadowing effects of surrounding objects [9]. The results suggested that the structures that experience a minimum of half-day direct insolation will support the growth of plants that mostly fall within moderate to very high DLI categories.…”
Section: Introductionmentioning
confidence: 98%